2008
DOI: 10.1097/brs.0b013e3181604501
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis of the Relationship Between the Grade of Disc Degeneration and Motion Unit of the Cervical Spine

Abstract: The changes that occur with disc degeneration progress from the normal state to an unstable phase with higher mobility and subsequently to an ankylosed stage. This study evaluated the contribution of different levels to the changes in overall motion that occur with degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 33 publications
7
76
0
Order By: Relevance
“…It also has implications for SCI, with cervical disc generation often associated with anterior compression of the spinal cord, and with accelerated progression in elderly persons (Okada et al, 2009). Slight to moderate disc degeneration can result in intervertebral instability (Dai, 1998;Miyazaki et al, 2008), which may potentially increase the risk of vertebral dislocations and neurological injuries associated with spinal cord shearing. In contrast, severe intervertebral disc degeneration is associated with increased intervertebral stability (Dai, 1998;Miyazaki et al, 2008) in part the result of osteophytosis at the discovertebral junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has implications for SCI, with cervical disc generation often associated with anterior compression of the spinal cord, and with accelerated progression in elderly persons (Okada et al, 2009). Slight to moderate disc degeneration can result in intervertebral instability (Dai, 1998;Miyazaki et al, 2008), which may potentially increase the risk of vertebral dislocations and neurological injuries associated with spinal cord shearing. In contrast, severe intervertebral disc degeneration is associated with increased intervertebral stability (Dai, 1998;Miyazaki et al, 2008) in part the result of osteophytosis at the discovertebral junction.…”
Section: Discussionmentioning
confidence: 99%
“…Slight to moderate disc degeneration can result in intervertebral instability (Dai, 1998;Miyazaki et al, 2008), which may potentially increase the risk of vertebral dislocations and neurological injuries associated with spinal cord shearing. In contrast, severe intervertebral disc degeneration is associated with increased intervertebral stability (Dai, 1998;Miyazaki et al, 2008) in part the result of osteophytosis at the discovertebral junction. Although they may assist in stabilizing the joint, osteophytic materials on posterior discovertebral junctions can result in cervical spondylosis and local pressure points that contribute to an increased risk of spinal cord compression injuries (Shedid and Benzel, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in the distribution of the cervical segmental mobility in the subjects with C5-6 stenosis were larger, mostly at the C4-5 segment, followed by C5-6. Miyazaki et al [16] reported that the C5-6 and C4-5 segments contributed the most to the total angular mobility of the cervical spine in the subjects with normal cervical intervertebral discs. However, the role of the C5-6 and C4-5 segments in the total angular mobility significantly decreased with severe intervertebral disc degenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is widely accepted that repetitive motion and micro-trauma accelerate degenerative changes in the spine. [24][25][26][27][28] Multiple studies have shown that a significant proportion of pre-operative range of motion remains following laminoplasty, from 61-81%. [29][30][31] Conversely, LF has been shown to allow less range of motion compared to laminoplasty.…”
Section: Discussionmentioning
confidence: 99%